The role of religious institutions in the process of reconciliation and peacebuilding - a case study of Bosnia and Herzegovina (Ahmići, Trusina and Bradina) - Jagiełło-Szostak, Anna (Teorija in praksa, 2020)
Bosnia and Herzegovina is a young, post-conflict and ethnically divided country in Europe. It is well known for being the scene of a conflict centred on religious divisions. For the researcher, this raises a number of interesting questions. What is the role of religious institutions in conflict and peacebuilding? Why is religion politicised? Can religious dialogue be perceived as a factor in the process of reconciling opposing ethnic communities; in this case, Serbs, Croats and Bosniaks? A section of this article is devoted to the stories of survivors from Bosniak, Croatian and Serbian families1. Each of these three ethnic groups suffered during the massacres in Ahmići, Trusina and Bradina, which took place in the first half of the 1990s. In addition, the authors analyse the role played by institutions like the Inter Religious Council in Sarajevo and the Maximilian Kolbe Foundation in order to assess their contribution to reconciliation and peacebuilding. In this regard, the purpose of the article is to conceptualise the issue of religious peacebuilding in the wider context of peace and conflict studies, as well as to call attention to the ubiquitous unobjective and unbalanced perceptions of the role of religion in contemporary conflicts and conflict resolution
Keywords: graditev miru; Ohranjanje miru; Peace-building; proces pomiritve; Reconciliation; Religious institutions; Sprava; spravni proces; Verske ustanove; vloga političnih institucij